2006
DOI: 10.1063/1.2345033
|View full text |Cite
|
Sign up to set email alerts
|

Heating and cooling in semiconductor structures by an electric current

Abstract: Articles you may be interested inCombining nanocalorimetry and dynamic transmission electron microscopy for in situ characterization of materials processes under rapid heating and cooling Rev. Sci. Instrum. 85, 084902 (2014); 10.1063/1.4892537 CFD modeling of thermoelectric generators in automotive EGR-coolers AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…Let us note that the obtained boundary conditions differ essentially from the boundary conditions used before, which were formulated without taking into account the nonequilibrium charge carriers (e.g., see [4,5]). In particular, unlike previous publications, new boundary conditions are formulated, Eqs.…”
Section: Structure Of the Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us note that the obtained boundary conditions differ essentially from the boundary conditions used before, which were formulated without taking into account the nonequilibrium charge carriers (e.g., see [4,5]). In particular, unlike previous publications, new boundary conditions are formulated, Eqs.…”
Section: Structure Of the Boundary Conditionsmentioning
confidence: 99%
“…[2], a new approach to the theory of thermoelectric cooling (heating) is proposed. Unlike traditional approaches [3][4][5][6][7][8][9], it takes into account the role of the nonequilibrium charge carriers. It is related with the impossibility to ignore the presence of minority charge carriers, because the current of minority charge carriers near the p-n junction has the same order of magnitude as the current of majority charge carriers [10], and the Peltier coefficients of the minority charge carriers are much larger than the Peltier coefficients of majority charge carriers [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Eqs. 3 and 4, η p is the phonon surface heat conductivity, η eh is the electron-hole surface heat conductivity, P 11 is the coefficient which corresponds to the electronphonon energy interaction on the interface between the electrons and phonons on the surface of the n-layer of the structure, P 12 is the coefficient that corresponds to the electron-phonon energy interaction on the interface between the electrons of the n-layer and the phonons of the p-layer, P 21 is the coefficient that corresponds to the hole-phonon energy interaction on the interface between the holes of the p-layer and the phonons of the n-layer; P 22 is the coefficient that corresponds to the hole-phonon energy interaction on the interface between the holes and phonons on the surface of the p-layer of the structure, Π e is the Peltier coefficient of the n-layer (Π e < 0), Π h is the Peltier coefficient of the p-layer (Π h > 0), and Π s is the Peltier coefficient of the interface [17]. The latter coefficient, according to its definition, can be positive or negative on the p-n junction.…”
Section: General Equations and Boundary Conditionsmentioning
confidence: 99%
“…VT, which should be added to the Joule heating [3e6]. Nevertheless, in a recently published work [9], it was clearly shown that this formulation of the Thomson effect is essentially erroneous, since, if consistently formulated, this effect may exist even if da/dT ¼ 0 and, moreover, the expression ÀTðda=dTÞ j ! VT is not a heat source/sink.…”
Section: Introductionmentioning
confidence: 98%